TRADITIONAL HEALTH CARE SYSTEM OF ODISHA TO CURE CHOLERA. - RAMA CHANDRA DASH; SATPAL SINGH BISHT (International Journal of Pharma and Bio Sciences, 2013)
Odisha state is rich in ethnomedicinal plants. This paper deals with ethnomedicinal uses and anti-cholerae properties of medicinal plants used by the rural tribal people of Odisha, India. The information about plants was collected by interviewing the local rural traditional practitioners. In the present study 26 plant species consisting of total no. of 26 genera belonging to 22 botanical families which are currently used in folk medicines for treatment of cholera in Odisha are documented. The present study reported 6 new ethnopharmacological plant species which are used and easily available but not documented by researchers of Odisha to cure cholera. The present investigation will help the researchers to document the traditional knowledge on the treatment of cholera. More attempts should be made to authenticate and evaluate the efficacy of these plants and products used by the tribal communities of Odisha.